ANALISIS TENTANG PEMENUHAN HAK AKSESIBILITAS NARAPIDANA KATEGORI DISABILITAS PADA LEMBAGA PEMASYARAKATAN - Mitro Subroto; Aditya Dwi Prahastomo (Universitas Wiralodra, 2025)
In this article, the author raises issues related to the fulfillment of accessibility rights for inmates with disabilities in correctional institutions. The background for choosing this topic is the author's interest in discussing the rights of inmates, particularly in the context of accessibility rights for inmates with disabilities in correctional institutions. Based on this background, the author raises several research questions, namely: Have the accessibility rights for inmates with disabilities, as regulated in Law No. 8 of 2016 on Persons with Disabilities, fulfilled the principle of equal treatment and service as stipulated in Law No. 22 of 2022 on Correctional Services? And Do the inmates' rights regulated in Law No. 22 of 2022 on Correctional Services already accommodate the rights of inmates with disabilities? This research uses a normative juridical method with a statutory approach. The research results show that the majority of correctional institutions in Indonesia have not fully implemented the principle of equal treatment and service because the accessibility rights for inmates with disabilities have not been adequately fulfilled. This is due to the lack of knowledge among officers, weak supervision, and limited government participation. Furthermore, the inmates' rights regulated in Law No. 22 of 2022 are not yet in line with the rights of inmates with disabilities as stipulated in Law No. 8 of 2016 due to the ongoing barriers in terms of facilities, infrastructure, regulations, and resources for inmates with disabilities.